2021
DOI: 10.3389/fmars.2021.707593
|View full text |Cite
|
Sign up to set email alerts
|

Circulation Pathways and Exports of Arctic River Runoff Influenced by Atmospheric Circulation Regimes

Abstract: River runoff supplies the Arctic Ocean with a large amount of freshwater and land-derived material, so it is important for both the physical and biogeochemical marine environment. In this study, we used wind perturbation simulations to elucidate the response of the circulation pathways and exports of Arctic river runoff to different atmospheric circulation regimes. Specifically, wind perturbations representing the negative and positive phases of the Arctic Oscillation and Beaufort High modes were imposed over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…This can be explained by the weak but positive sea level pressure anomaly in the central Arctic basin averaged over the past 20 years (Figure S9). The sea level pressure anomaly roughly resembles a negative Arctic Oscillation pattern, which tends to shift the surface freshwater circulation pathway from the Amerasian Basin towards the Eurasian Basin (Wang et al, 2021b). The sea ice decline completely changes this tendency.…”
Section: Impact Of Sea Ice Decline On Arctic Atlantificationmentioning
confidence: 90%
See 3 more Smart Citations
“…This can be explained by the weak but positive sea level pressure anomaly in the central Arctic basin averaged over the past 20 years (Figure S9). The sea level pressure anomaly roughly resembles a negative Arctic Oscillation pattern, which tends to shift the surface freshwater circulation pathway from the Amerasian Basin towards the Eurasian Basin (Wang et al, 2021b). The sea ice decline completely changes this tendency.…”
Section: Impact Of Sea Ice Decline On Arctic Atlantificationmentioning
confidence: 90%
“…Changes in ocean inflow from the North Pacific and North Atlantic could also influence the upper ocean circulation in the Arctic Ocean (Spall, 2020;Karami et al, 2021;Wang et al, 2021b). For example, stronger Pacific Water inflow through the Bering Strait can increase the sea surface height along the continental slope of the Canada Basin so that the ocean circulation towards the Canadian Arctic Archipelago and Fram Strait is strengthened (Spall, 2020;Wang et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the authors, the mean FWC trend calculated using S ref = 35.0 based on monthly gridded fields between 1992 and 2012 was about 600 ± 300 km 3 yr −1 , which is equivalent to the 16,800 ± 8400 km 3 increase in FWC estimated for the period covered by our observations. We speculate that the freshening in the Arctic Ocean will continue since several observation-and model-based studies have suggested an increasing trend in the freshwater supply to the Arctic under warming climate due to increasing atmospheric moisture transport from lower latitudes and increased river runoff [50][51][52][53][54].…”
Section: Long-term Fwc Changesmentioning
confidence: 96%